Porous Rock Fracture Mechanics : with Application to Hydraulic Fracturing, Drilling and Structural Engineering - Shojaei, Amir K., editor 649355; Shao, Jianfu, editor 649356; ScienceDirect (Online service) 7722 (Cambridge : Woodhead Publishing, 2017)
orous Rock Failure Mechanics: Hydraulic Fracturing, Drilling and Structural Engineering focuses on the fracture mechanics of porous rocks and modern simulation techniques for progressive quasi-static and dynamic fractures. The topics covered in this volume include a wide range of academic and industrial applications, including petroleum, mining, and civil engineering.